Singularity: Rethinking the Software Stack - Hunt, Galen; Larus, Jim (ACM SIGOPS Operating Systems Review, 2007)
Every operating system embodies a collection of design decisions. Many of the decisions behind today’s most popular operating systems have remained unchanged, even as hardware and software have evolved. Operating systems form the foundation of almost every software stack, so inadequacies in present systems have a pervasive impact. This paper describes the efforts of the Singularity project to re-examine these design choices in light of advances in programming languages and verification tools. Singularity systems incorporate three key architectural features: software-isolated processes for protection of programs and system services, contract-based channels for communication, and manifest-based programs for verification of system properties. We describe this foundation in detail and sketch the ongoing research in experimental systems that build upon it.